Toxicity, biodistribution and oxidative damage caused by zirconia nanoparticles after intravenous injection - Yang Y (Dove Medical Press, 2019)
Yue Yang,1,2 Huihui Bao,1 Qianqian Chai,3 Zhiwen Wang,2 Zhenning Sun,2 Changhui Fu,3 Zhaoping Liu,1 Zhongjie Liu,2 Xianwei Meng,3 Tianlong Liu21China National Center for Food Safety Risk Assessment, Beijing 100022, People’s Republic of China; 2Key Laboratory of Animal Epidemiology of Ministry of Agriculture, College of Veterinary Medicine, China Agricultural University, Beijing 100193, People’s Republic of China; 3Laboratory of Controllable Preparation and Application of Nanomaterials, Technical Institute of Physics and Chemistry, Chinese Academy of Sciences, Beijing 100190, People’s Republic of ChinaBackground: As a promising nanomaterial for biomedical applications, zirconia nanoparticles (ZrO2) have aroused concern recently, but the toxicity of ZrO2 in vivo has received little attention.Purpose: The aim of this study is to demonstrate the systematic single dose toxicity, biodistribution and oxidative damage of ZrO2 in vivo after intravenous injection in mice.Materials and methods: Ten ICR mice were used at the high dose of ZrO2 including 600, 500, 400 and 300mg/kg. Maximum tolerated dose (MTD) of 150 nm ZrO2 was determined as 500mg/kg. Hematology analysis and blood biochemical assay were determined for the evaluation of oxidative damage caused by ZrO2. Biodistribution of ZrO2 was investigated by ICP-OES and TEM.Results: Mice treated with higher dose (500mg/kg) showed significant spread in white blood cell counts (p<0.05). Especially, the serum ALT levels of 500mg/kg groups increased significantly (p<0.05) compared with the control group. ZrO2 particles would not induce any changes in appearance and micromorphology of liver at 100 and 350mg/kg. Spleen samples showed no significant changes in micromorphology of the lymphoid follicles and in the size of the red pulp after injection of ZrO2 at all doses. The serum of ZrO2-treated animals (350 and 500mg/kg) has reduced levels of SOD compared to the control group (p<0.05). ZrO2 persists in membrane-enclosed vesicles called lysosomes in the liver and spleen macrophages without abnormal changes of ultrastructure.Conclusion: These findings would contribute to the future development of ZrO2-based drug delivery system and other biomedical applications.Keywords: zirconia nanoparticles, toxicity, biodistribution, oxidative damage, ICP-OES